Sosialisasi Pemanfaatan Digital Marketing Pada (UMKM) Toko Baju Tulip Bengkulu - Siboro, Nadia Sauli Yanti Br.; Susanti, Nerry; Effendi, Bahman; Effendi, Yanto; Herlin, Herlin (LPPM Universitas Dehasen Bengkulu, 2024)
This proposal outlines a socialization plan for the use of digital marketing at Toko Baju Tulip in Bengkulu. The main objective is to improve the knowledge and skills of the store owner and employees in using digital platforms to promote and sell their products. With this training, the store is expected to increase sales and expand market reach. This research uses a descriptive qualitative method. The power needed as a research knife is primary data which the author obtained by observation and interviews with parties related to this research. Secondary data is obtained from various books, journal articles, and other supporting literature. While the results of this study are in the form of: first, based on the opinions of MSME business owners who improve their performance through digital marketing only by creating interesting content and easy for people to remember. Second, based on the opinions of MSME enthusiasts and customers, “Toko Baju Tulip” can reduce costs and can be a strong competitor for those who do not use digital marketing. Third, based on the opinion of the general public, MSMEs do need increased work in terms of digital marketing to introduce the product identity and corporate identity of MSMEs in an era that uses the internet.